The Causal Relationship among CO2 Emission, Oil Consumption and Economic Growth in Thailand: ARDL Bound Testing Approach - Bunnag, Tanattrin (International Journal of Energy Economics and Policy, 2021)
This paper examined the causal relationships among CO2 emission, oil consumption, and economic growth in Thailand. The data used in this study was the yearly data from 1971 to 2014. The ARDL and Granger causality approaches were employed. Overall, the empirical results showed that it had established a long-run relationship among CO2 emission, oil consumption, and economic growth. Moreover, there is a one-way (unidirectional) short-run Granger causality between oil consumption and CO2 emission. In addition, there is a one-way (unidirectional) long-run Granger causality between oil consumption and CO2 emission and a one-way long-run causal route from oil consumption to economic growth and CO2 emission. Finally, the empirical results of this study provided that policymakers need to improve efficiency in oil consumption not to increase CO2 emissions. Furthermore, policymakers should endeavor to overcome the constraints on oil consumption to achieve economic growth. Keywords: oil consumption, CO2 emission, economic growth, ARDL, and Granger causality approaches JEL Classifications: C13, C20 DOI: https://doi.org/10.32479/ijeep.11811